1999
DOI: 10.1002/(sici)1097-4628(19990808)73:6<1007::aid-app19>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cotton-bearing DEAE, carbamoyethyl, carboxyethyl, and poly(acrylamide) graft for utilization in dye removal

Abstract: Cotton cellulose in the fabric form was subjected to etherification and grafting reactions with the purpose of obtaining cotton with ionic properties. Thus, cottons bearing DEAE, carbamoylethyl, and carboxyethyl groups, along with partially hydrolyzed poly(Aam) graft, were synthesized. The ability of these cotton substrates to function as ion exchangers, particularly for removal of direct, basic, acid, and reactive dyes from aqueous solution was examined. The obtained results reveal that such modifications inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…The reduction caused by modification of carboxyl (T2) groups may be due to the similar mechanism. The carboxyl groups on aerobic granules may be the proper binding sites for MG, which was consistent with the results obtained from El-Hilw's research (El-Hilw, 1999). Furthermore, after amine group modification (T1), the biosorption was sharply decreased, which demonstrated that the amine groups also could interact with the Dye + .…”
Section: Mgsupporting
confidence: 89%
“…The reduction caused by modification of carboxyl (T2) groups may be due to the similar mechanism. The carboxyl groups on aerobic granules may be the proper binding sites for MG, which was consistent with the results obtained from El-Hilw's research (El-Hilw, 1999). Furthermore, after amine group modification (T1), the biosorption was sharply decreased, which demonstrated that the amine groups also could interact with the Dye + .…”
Section: Mgsupporting
confidence: 89%
“…Due to these reasons the dye concentration in the discharged water should be controlled. Grafted polymers were also tested in dye removal and grafted cellulose with appropriate functional groups was found to be a good sorbent (El-Hilw, 1999;El-Salmawi et al, 2001;Bouzaida and Rammah, 2002;Sokker et al, 2004;Aly et al, 2005;Hashem et al, 2005;Gupta and Suhas, 2009). When the binding to the grafted material takes place with weak forces, the uptake may be reversible and during solvent regeneration the dye is collected in concentrated solution.…”
Section: Adsorption Of Substances Other Than Heavy Metal Ionsmentioning
confidence: 99%
“…그 동안 cotton은 세포 고정화 담체로서 보다는 분리/정제를 위한 담체로서 많이 사용되어져 왔다 [4,6,7,15,19] 에 옮겨 배양을 시작하였으며, flask 배지 내의 free cell 농도, glucose와 xylose의 소비, 그리고 ethanol 생성을 관찰하였다 (Fig. 6, 7).…”
Section: 서 론unclassified